2017
DOI: 10.1038/s41598-017-00687-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative chromatin proteomics reveals a dynamic histone post-translational modification landscape that defines asexual and sexual Plasmodium falciparum parasites

Abstract: Gene expression in Plasmodia integrates post-transcriptional regulation with epigenetic marking of active genomic regions through histone post-translational modifications (PTMs). To generate insights into the importance of histone PTMs to the entire asexual and sexual developmental cycles of the parasite, we used complementary and comparative quantitative chromatin proteomics to identify and functionally characterise histone PTMs in 8 distinct life cycle stages of P. falciparum parasites. ~500 individual histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
147
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(172 citation statements)
references
References 88 publications
14
147
1
Order By: Relevance
“…The stage-specific inhibition profiles observed for the wide variety of epi-drug inhibitor classes support the findings that the parasite makes use of altered epigenetic regulatory mechanisms to differentiate itself during asexual proliferation and sexual differentiation (7,48,49). Selective Plasmodium inhibition was only shown for 6 compounds of the series, which suggests that the epigenetic modulators targeted by these compounds (HKMT, HDAC and PRMT) show diversity between the parasite and human homologues, as previously shown by the unique set of Plasmodium-specific epigenetic factors that differs vastly from those in its mammalian host (39).…”
Section: Histone-associated Epigenetic Regulators Remain Overrepresensupporting
confidence: 63%
See 2 more Smart Citations
“…The stage-specific inhibition profiles observed for the wide variety of epi-drug inhibitor classes support the findings that the parasite makes use of altered epigenetic regulatory mechanisms to differentiate itself during asexual proliferation and sexual differentiation (7,48,49). Selective Plasmodium inhibition was only shown for 6 compounds of the series, which suggests that the epigenetic modulators targeted by these compounds (HKMT, HDAC and PRMT) show diversity between the parasite and human homologues, as previously shown by the unique set of Plasmodium-specific epigenetic factors that differs vastly from those in its mammalian host (39).…”
Section: Histone-associated Epigenetic Regulators Remain Overrepresensupporting
confidence: 63%
“…The primary evaluation of the activity of epi-drugs against the multiple life cycle stages indicated that early stage gametocytes were particularly susceptible to epi-drug inhibition, supported by reports of a unique epigenetic repertoire associated with these stages, where the switch between asexual and sexual stages was accompanied by dynamic histone PTM landscape alterations (7). The differentiation between the compounds active against the different life cycle stages correlates with unique and stage-specific histone PTM dynamics during the parasite's life cycle, with clear peaks abundances for some epigenetic marks associated with particular life cycle stages (7,48,49) and highlights the importance of these activities to parasite development.…”
Section: Histone-associated Epigenetic Regulators Remain Overrepresenmentioning
confidence: 91%
See 1 more Smart Citation
“…(C) The genes expressed during maturation (cluster 10) showed a significant association ( P <0.0001, two-tailed Fisher’s exact test) with genes stabilized post-transcriptionally during commitment (18) and H3K36me3-associated genes in asexual development (16,73) before a sharp increase at stage IV-V of development (dashed line). Blocks indicate the timing of stabilization of the transcripts (18) or abundance of the H3K36me3 mark (65) and the overlap between the 3 datasets are indicated in the Venn diagram. Genes of interest within the three functional datasets are highlighted in heatmap.…”
Section: Resultsmentioning
confidence: 99%
“…The histone core protein and N‐terminal tails are subjected to many modifications including methylation, acetylation, and phosphorylation . At least 500 individual histone PTMs on different amino acid positions were identified recently on P. falciparum histone proteins in a proteomic screen, and so far 106 PTMs were experimentally validated in the follow up studies . The acetylation of histone tails is primarily involved in the gene activation process, whereas methylation is involved in both gene activation and suppression.…”
Section: Introductionmentioning
confidence: 99%